Exergoeconomic and environmental analyses of high carbon ferrochrome production process - Kapan, Sinan; Celik, Nevin; Camdali, Unal (Inderscience Enterprises Ltd, 2025)
In this study, exergy and cost balance of a submerged arc furnace (SAF) producing high carbon ferro chrome (HC FeCr) is evaluated. Exergoeconomic analysis of the HC FeCr was carried out using real operating data. The exergy cost of HC FeCr is found as $9,929.32/h, and the cost per unit exergy is $125.74/GJ. The unit cost and hourly levelised cost of exergy loss are $69.32/GJ and $2,401.13/h, respectively. The resource reuse rate is 84.26%. The amount of CO2 is 958.12 kg-CO2/HC FeCr-ton. The capital cost flow is very high, due to hourly levelised operating and maintenance costs.
Keywords: high carbon ferrochrome; submerged arc furnace; SAF; exergoeconomics; environmental